2016
DOI: 10.1007/s00246-016-1524-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Pacing via the Umbilical Vein and Subsequent Permanent Pacemaker Implantation in a Neonate

Abstract: A dying neonate with congenital complete atrioventricular block underwent an emergency temporary pacing via the umbilical vein 1 h after birth. Implantation of a permanent epicardial pacemaker system was performed at the age of 10 days. During the follow-up period of 3 months, the child had been growing well with the VVIR pacemaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…When there is symptomatic or worrying bradycardia or tachycardia that ineffective to drug therapy or requiring repeated cardioversion, temporary pacemakers are needed. As an effective means of transition and protection, temporary pacemakers are used to improve success rate of rescue and improve prognosis (3)(4)(5)(6)(7)(8)(9)(10). However, some difficulties are involved in the temporary pacemaker implantation in children, such as small physique, cardiac anomaly, lower tolerance to disease, many complications and so on and the number of pediatric pacemakers implanted is still relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…When there is symptomatic or worrying bradycardia or tachycardia that ineffective to drug therapy or requiring repeated cardioversion, temporary pacemakers are needed. As an effective means of transition and protection, temporary pacemakers are used to improve success rate of rescue and improve prognosis (3)(4)(5)(6)(7)(8)(9)(10). However, some difficulties are involved in the temporary pacemaker implantation in children, such as small physique, cardiac anomaly, lower tolerance to disease, many complications and so on and the number of pediatric pacemakers implanted is still relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that it is very difficult to conduct transvenous pacing via the femoral vein or internal jugular vein in neonates; however, the umbilical vein approach is simple and useful. 3,4 A few reports have detailed emergency pacing via the umbilical vein of neonates. None have described neonates with complex CHD.…”
mentioning
confidence: 99%